Study of the Efficacy of Colistin against Wound Contamination by Acinetobacter baumannii - Hamad, Sara Salam; Hussein, Arwa Alaa; Razzaq, Alaa Siham Abdul (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2025)
Background.Acinetobacter baumannii is a multidrug-resistant (MDR) Gram-negative pathogen commonly associated with wound infections, particularly in hospital and battlefield settings. Due to its resistance to multiple antibiotic classes, treatment options are limited. Colistin (polymyxin E), a last-resort antibiotic, has been reintroduced for treating MDR A. baumannii infections. Objective: This study aimed to evaluate the efficacy of colistin against A. baumannii isolated from wound contamination cases. Methods: A total of (30) wound swabs were collected from patients with clinical signs of infection. Isolation and identification of (10) isolations of A. baumannii and (20) were different species. A. baumannii conducted using standard microbiological and biochemical methods, followed by confirmation via Vitek 2 compact. Antimicrobial susceptibility testing (AST) was performed using the Kirby-Bauer disk diffusion method, and colistin minimum inhibitory concentration (MIC) was determined by broth microdilution following CLSI/EUCAST guidelines. Results: According to this study on Acinetobacter baumannii, the bacteria might stop the bacteria's development at various colistin concentrations. In contrast to 500 µg/ml, the higher concentration (1000 µg/ml) generated a wider zone of inhibition, indicating dose-dependent antibacterial action. A wider zone of inhibition was seen at the higher concentration, suggesting dose-dependent antibacterial action. The study also discovered that following skin damage, skin cells progressively restored to their original architecture, however inflammatory cells and cellular debris persisted. Significant necrosis was seen in the second group, suggesting a serious inflammatory reaction. The third group displayed epidermal cell regeneration, with the group that received 1000 µg/ml of colistin exhibiting more noticeable regeneration. Conclusion: Colistin remains a highly effective antibiotic against MDR A. baumannii in wound infections. However, its use should be monitored due to the risk of emerging resistance and potential nephrotoxicity. Regular surveillance and antibiotic stewardship programs are essential to preserve their efficacy